2018
DOI: 10.1111/josh.12583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleep Duration, Diet, and Physical Activity on Obesity and Overweight Elementary School Students in Shanghai

Abstract: We found that age, sex, sleep, and some dietary habits impacted weight, and suggests that specific cultural and economic factors may impact risk of a child being overweight or obese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 31 publications
(66 reference statements)
3
26
0
2
Order By: Relevance
“…The 2014 Sleep in America ® Poll revealed that nearly one in three children age 6 to 11 years in the Unites States gets 8 h or less of sleep each night [ 46 ], falling short of the National Sleep Foundation’s recommended 9 to 11 h per night [ 47 ]. The link between short sleep duration and increased BMI is well established [ 48 ]. Decreased sleep duration associated with SSB consumption may further exacerbate the association between SSB consumption and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The 2014 Sleep in America ® Poll revealed that nearly one in three children age 6 to 11 years in the Unites States gets 8 h or less of sleep each night [ 46 ], falling short of the National Sleep Foundation’s recommended 9 to 11 h per night [ 47 ]. The link between short sleep duration and increased BMI is well established [ 48 ]. Decreased sleep duration associated with SSB consumption may further exacerbate the association between SSB consumption and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Restructuring the schoolyard offering more space for PA (eg, marking with cones activity zones) Preparing active games or interclass competitions for the recess Challenging the students to be active during recess, remind it frequently (eg, placing a sheet in the classroom with some reminders). Offer feedback …”
Section: Implications For School Healhmentioning
confidence: 99%
“…Current recommendations, considering children’s overall well-being as well as cognitive, emotional and physical health, advocate nine to eleven hours of sleep per day for 6- to 13-year-olds [27]. Based on those recommendations, internationally, numerous studies investigated the influence of sleep on obesity and obesity-related behaviours in children [28, 29]. In German as well as Chinese primary school children for instance, a daily sleep duration of 10 h or less was significantly associated to being overweight or obese [26, 28].…”
Section: Introductionmentioning
confidence: 99%